WORD AND EXCELL TRAINING PROGRAM AT ELEMENTARY SCHOOL N 04 KOTA BENGKULU - Putra, Erwin Dwika; Marissa Utami (Lembaga Penelitian Pengabdian Masyarakat Penerbitan dan Percetakan Indonesian Scholar Khiar Wafi (LPPMPP IKHAFI), 2024)
Mastery of Microsoft Word and Excel applications is essential in supporting administrative tasks and data management in educational settings. However, the limited ability of teachers and administrative staff to use this software is still a challenge in Sekolah Dasar Negeri 04 Kota Bengkulu. This community service activity aims to improve the basic skills of using Microsoft Word and Excel for teachers and administrative staff at the school. The training was conducted in several sessions covering the introduction and practice of the main features of Microsoft Word, such as setting document formats, creating tables, and using symbols, as well as Microsoft Excel, which includes creating tables, using basic formulas, and creating simple graphs. The results of the training showed an increase in participants' ability to manage documents and data independently, such as the preparation of reports, grade lists, and student attendance data. The evaluation of this activity showed that participants found it helpful in improving their digital skills, but further training is still needed to explore more complex features. This training program is expected to provide long-term benefits for schools in improving administrative efficiency and supporting the quality of digital-based learning.